New partnership in Cameroon - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
With a far flung reputation for building up farmers organisations in Cameroon, the organ known as the Network for Farmers Agriculture and Modernisation in Africa/ Cameroon (APM/Cameroon) has joined CTA in a partnership agreement. Up to October...